Spectrophotometric estimation of ambroxol hydrochloride and cetirizine hydrochloride in tablets - Bhatia, Neela Manish; Ganbavale, Santosh Kumar; More, Harinath Nivrutti (Asian Journal of Pharmaceutics (AJP), 2014)
A simple, rapid, accurate, precise and reproducible simultaneous equation method has been developed for simultaneous estimation of ambroxol hydrochloride and cetirizine hydrochloride in tablets. Ambroxol hydrochloride has absorbance maxima at 243 nm, while cetirizine hydrochloride has absorbance maxima at 229 nm in glass-distilled water. The method developed involves no separation or extraction process.The proposed methods were successfully applied to the determination of ambroxol hydrochloride and cetirizine hydrochloride in tablets, with high percentage of recovery, good accuracy, and acceptable precision. Different analytical performance parameters such as linearity, precision, accuracy, limit of detection, limit of quantitation, and robustness were determined according to International Conference on Harmonization ICH Q2B guidelines. Results of analysis of formulation given as percentage of label claim ± relative standard deviation were found to be 99.27 ± 0.8083 and 102.43 ± 1.5357 for ambroxol hydrochloride and cetirizine hydrochloride respectively. Results of recovery studies given as percentage of label claim ± relative standard deviation were found to be 99.88 ± 0.3811 and 100.36 ± 2.0480 for ambroxol hydrochloride and cetirizine hydrochloride respectively.